Canonical Wnt Signaling Promotes Formation of Somatic Permeability Barrier for Proper Germ Cell Differentiation - Chen, Ting-An; Lin, Kun-Yang; Yang, Shun-Min; Tseng, Chen-Yuan; Wang, Yu-Ting; Lin, Chi-Hung; Luo, Lichao; Cai, Yu; Hsu, Hwei-Jan (Frontiers in Cell and Developmental Biology, 2022)
Morphogen-mediated signaling is critical for proper organ development and stem cell function, and well-characterized mechanisms spatiotemporally limit the expression of ligands, receptors, and ligand-binding cell-surface glypicans. Here, we show that in the developing Drosophila ovary, canonical Wnt signaling promotes the formation of somatic escort cells (ECs) and their protrusions, which establish a physical permeability barrier to define morphogen territories for proper germ cell differentiation. The protrusions shield germ cells from Dpp and Wingless morphogens produced by the germline stem cell (GSC) niche and normally only received by GSCs. Genetic disruption of EC protrusions allows GSC progeny to also receive Dpp and Wingless, which subsequently disrupt germ cell differentiation. Our results reveal a role for canonical Wnt signaling in specifying the ovarian somatic cells necessary for germ cell differentiation. Additionally, we demonstrate the morphogen-limiting function of this physical permeability barrier, which may be a common mechanism in other organs across species.